Phlebotomus papatasi exposure cross-protects mice against Leishmania major co-inoculated with Phlebotomus duboscqi salivary gland homogenate - Lestinova, Tereza; Vlkova, Michaela; Votypka, Jan; Volf, Petr; Rohousova, Iva (Acta tropica, 2015)
Leishmania parasites are inoculated into host skin together with sand fly saliva and multiple exposures to uninfected sand fly bites protect mice against Leishmania infection. However, sand fly vectors differ in composition of the saliva and therefore the protection elicited by their salivary proteins was shown to be species-specific. On the other hand, the optimal vaccine based on sand fly salivary proteins should be based on conserved salivary proteins conferring cross-reactivity. In the present study we therefore focused on cross-protective properties of saliva from Phlebotomus papatasi and Phlebotomus duboscqi, the two natural vectors of Leishmania major. Two groups of mice exposed to bites of P. papatasi and two control, non-immunized groups were infected with L. major promastigotes along with either P. papatasi or P. duboscqi salivary gland homogenate. All mice were followed for the development of Leishmania lesions, parasite burdens, specific antibodies, and for production of NO, urea, or cytokines by peritoneal macrophages. Protection against Leishmania infection was observed not only in exposed mice challenged with homologous saliva but also in the group challenged with P. duboscqi saliva. Comparing both exposed groups, no significant differences were observed in parasite load, macrophage activity, or in the levels of anti-L. major and anti-P. papatasi/P. duboscqi antibodies. This is the first study showing cross-protection caused by salivary antigens of two Phlebotomus species. The cross-protective effect suggests that the anti-Leishmania vaccine based on P. papatasi salivary proteins might be applicable also in areas where L. major is transmitted by P. duboscqi.
Keywords: zvířata; Leishmania major; Antigens; Species Specificity; cytokiny; Salivary Proteins and Peptides; leishmanióza; Mice; Leishmaniasis; Animals; Cross Protection; Antibodies, Protozoan; protilátky protozoální; Cytokines; druhová specificita; Salivary Glands; antigeny; zkřížená ochrana; slinné žlázy; myši; Phlebotomus; slinné proteiny a peptidy